EKSPOSUR RISIKO INSTRUMEN DERIVATIF, VOLATILITAS NILAI PERUSAHAAN DAN OPINI AUDIT GOING CONCERN - Nurul Izzakiah; Akram Akram; Elin Erlina Sasanti (Jurnal Riset Akuntansi, 2017)
The objective of this study is to determine the influence of derivative instruments risk exposure to the volatility of the company. This study also aimed to determine the influence of the volatility of the company on the going concern audit opinion as well as the influence of derivative instruments risk exposure on the going concern audit opinion with volatility of the company as intervening variable. Derivative instruments risk exposure variable in the study is represented by the cost of capital, short- term liquidity, fluctuations in earnings and debt levels. The sample consisted of 28 companies listed in Indonesia Stock Exchange (IDX). Hypotheses testing for the first model based on multiple regression analysis suggest that the cost of capital, short-term liquidity, fluctuations in earnings and debt levels has no significant influence on the volatility of the company. Hypotheses testing for the second model also suggest that the volatility of the company do not affect the going concern audit opinion. However, the results based on path analysis suggest that short-term liquidity; fluctuations in earnings and debt levels indirectly influence the going concern audit opinion with the volatility of the company as an intervening variable.